Anatomical and morphometrical evaluation of the jugular tubercle. (August 2014) - Turan Suslu, Hikmet; Gayretli, Ozcan; Coskun, Osman; Bozbuga, Mustafa; Serifoglu, Luay; Gurses, Ilke Ali
Abstract Background. The jugular tubercle (JT) is an important part of the craniovertebral junction. The removal of the JT in the far-lateral approach provides a significant increase in the operative space. The purpose of this morphometrical study was to define the anatomical variations of the JT. Methods. Thirty-eight dry skulls were included in this study. Seven anatomical parameters were defined and analyzed. The JT, hypoglossal canal (HC), jugular bulb, condylar fossa, occipital condyle (OC), internal jugular foramen, and condylar canal were selected as landmarks. The measurements were made separately for the right and the left sides. Results. Significant morphological variations in the JT were noted. A protuberance was apparent on the JT and classified according to its shape, size, and number. Morphological differences of protuberance of JT were described and classified into seven different types as follows: flat (Type I), sharp (Type II), circular (Type III), pin-point (Type IV), large (Type V), double (Type VI), and unclassified (Type VII). The HC was observed in all specimens. To define the relationship between the JT and the intracranial orifice of the HC, four localizations were identified. To define the relationship between the JT and the intracranial orifice of the HC. Conclusions. Variations of the JT and the relationship of the JT to the neighboring bone and neural structures are important for modifications of the far-lateral approach. This study presents a detailed anatomical analysis of the shape, size, and orientation of the JT with a new description of protuberance of JT classified into seven types.